2009
DOI: 10.1139/b08-130
|View full text |Cite
|
Sign up to set email alerts
|

Undifilum, a new genus for endophyticEmbellisia oxytropisand parasiticHelminthosporium bornmuellerion legumes

Abstract: Fungal endophytes of Oxytropis kansuensis Bunge from China, previously described as Embellisia oxytropis Q. Wang, Nagao & Kakish, and endophytes of Oxytropis sericea Nutt. and Oxytropis lambertii Pursh from the United States were compared and are reported here as conspecific members of a new genus in the Pleosporaceae, Undifilum, based on morphological and molecular analyses. Morphological comparisons revealed characters that are similar to those of the genus Embellisia including conidia ovate to obclavate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 23 publications
7
101
0
1
Order By: Relevance
“…The latter are forage plants whose consumption by livestock is associated to the syndrome of locoism. It has been observed that a fungal endophytic species occurring in locoweeds, the vertically-transmitted Undifilum oxytropis [324,325], previously described as Embellisia sp. [326,327], is capable to produce swainsonine in vitro.…”
Section: Other Alkaloidsmentioning
confidence: 99%
“…The latter are forage plants whose consumption by livestock is associated to the syndrome of locoism. It has been observed that a fungal endophytic species occurring in locoweeds, the vertically-transmitted Undifilum oxytropis [324,325], previously described as Embellisia sp. [326,327], is capable to produce swainsonine in vitro.…”
Section: Other Alkaloidsmentioning
confidence: 99%
“…Swainsonine-producing endophytes isolated from Oxytropis in China were essentially identical to those collected in the United States, and both were given the name Undifilum oxytropis. 3 Endophytes isolated from Astragalus species will likely be classified into several additional species of the fungal genus.…”
Section: Genetics Of the Fungal Endophytes Of Locoweed By R Creamermentioning
confidence: 99%
“…that produces the swainsonine (Braun et al, 2003;Wang et al, 2006;Pryor et al, 2009;Yu et al, 2010;Lu et al, 2012a;Creamer and Baucom, 2013;Grum et al, 2013;Woudenberg et al, 2013). Although not every plant in a population is toxic or contains the endophyte, all toxic plants that contain swainsonine have been shown to contain a swainsonine-producing fungal endophyte (Cook et al, 2011Achata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of fungal endophytes includes species diversity in colonization of host plants and diversity in the distribution of fungal endophytes within different tissues of host plants. This diversity could be due to differences in the host plants and natural factors, such as geographical location and climate, in addition to presence of other organisms (Tiina et al, 2013 (Pryor et al, 2009;Baucom et al, 2012). Alternaria sect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation